Handbook of research on green economic development initiatives and strategies - (:unkn) unknown (IGI Global, 2016)
Climate change is one of the most pressing issues facing the world today, as it affects all sectors of life, be it global economics or human rights activism; timely action is required to avoid global catastrophe. Understanding the importance of climate change mitigation, renewable energies, clean technologies, and green development has become necessary for effective leadership. The Handbook of Research on Green Economic Development Initiatives and Strategies provides the necessary information to reduce the climate change vulnerability of socio-economic systems in the most cost-effective manner. This handbook of research is ideal for policy makers, non-governmental organizations (NGOs), government agencies, businesses, and professionals looking to temper the effects of climate change. © 2016 by IGI Global. All rights reserved.